2004
DOI: 10.2139/ssrn.715981
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Local Economic Development: Beyond Productivity Spillovers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…Similar to employment, sales competition could potentially capture both positive spillovers, i.e., domestic firms are spurred to become more efficient or to upgrade their technology due to competition (Blomström and Kokko, 1998) or negative spillovers such as market stealing or congestion pricing (Aiken and Harrison, 1999;Görg and Greenaway, 2004;Görg and Strobl, 2005). Our empirical results reveal that negative spillovers in this case are the dominant effect in both limited and wider geographic scopes in our study.…”
Section: Introductionmentioning
confidence: 68%
“…Similar to employment, sales competition could potentially capture both positive spillovers, i.e., domestic firms are spurred to become more efficient or to upgrade their technology due to competition (Blomström and Kokko, 1998) or negative spillovers such as market stealing or congestion pricing (Aiken and Harrison, 1999;Görg and Greenaway, 2004;Görg and Strobl, 2005). Our empirical results reveal that negative spillovers in this case are the dominant effect in both limited and wider geographic scopes in our study.…”
Section: Introductionmentioning
confidence: 68%
“…Some of the research using panel data showed the existence of positive effects or assuming certain factors such as absorption capacity (Kinoshita 2001, Girma 2005) and the level of technological gap between foreign and domestic companies (Kokko,Tansini and Zejan 1994;Basile,Castellani and Zanfei 2003). In a detailed review of the research on the spillover effects related to FDI, Gorg and Strobl (2004) concluded that the results of productivity spillover does not depend on whether data at the level of industries or companies were used but on whether methods of comparative data or panel data were used. Of the 40 studies, in 19 there has been a statistically significant conclusions about the existence of positive spillover effects, 15 studies found no significant spillover effects and 6 studies found evidence of negative spillover effects.…”
Section: Literaturereviewmentioning
confidence: 99%
“…Variables for detecting vertical spillover effects are designed using input-output table. Some studies have found evidence of positive vertical spillover effects (Schoors and van der Tol (2002) for Hungary, Javorcik, Saggi and Spatareanu (2004) for Lithuania; Blalock and Simon (2009) for Indonesia. Other studies, however, have come to the different results.…”
Section: Literaturereviewmentioning
confidence: 99%
“…In a similar way, Gorg and Strobl concluded that FDI can be of use to local companies, not only through transfer of technology, but also through the so-called externalities. In other words, foreign investors increased the demand for local products and services that are used in everyday business, primarily at the local level, which enabled local companies to increase productivity [6].…”
Section: Fdi and Economic Development Of The Host Countrymentioning
confidence: 99%